India's Water Economy : Bracing for a Turbulent Future - Ruiz-Mier, Fernando (World Bank, Washington, DC, 2012)
For 150 years India has made major investments in large-scale water infrastructure, bringing water to areas that previously lacked it. The results have been spectacular, both nationally, through the production of food grains and electricity, and regionally, as projects have generated direct and indirect economic benefits. Once-arid areas have become centers of economic growth, while historically well-watered areas have seen slower progress. The poor have benefited greatly from such investments. Poverty in irrigated districts is one-third that in unirrigated districts. India needs more water-storage capacity, appropriately scaled. The present system is capable of storing only 30 days of rainfall, compared with some 900 days in the major river basins of arid areas of developed countries. And the need for storage will grow, as global climate change begins to be felt: rapid glacial melting is likely to occur in the western Himalayas in coming decades, accompanied by greater variability of rainfall in large parts of the subcontinent. But India's water management system is not sustainable. Without significant increases in investment and profound changes in the way India's water institutions are run, the country will face water shortages and environmental problems that will gravely affect its people and its economy.